Lease Finance in Nigeria: Current Status, Challenges and Future Prospects - Umar Farouk Abdulkarim; L. Mohammed; A. Musa-Mubi (Journal of Accounting Research, Organization and Economics, 2020)
Objective – The Leasing industry in Nigeria is witnessing increased demand for assets under a given prevalence of rising domestic costs of purchase, shortage of foreign exchange for imports as well as persistent depreciation of the Naira. The objective of this paper is to analyze the current state of lease financing in Nigeria, the prospects and challenges with a view to assess the capacity of the industry to continue to provide this form of finance. Design/methodology –The paper adopts an exploratory research design with references to publications, websites and research articles relevant to the subject matter. A number of relevant publications on leasing in Nigeria were duly explored. Results – Our findings show that, the volume of lease finance has consistently grown over the last 14 years (2005-2018). Finance leases volume totaled 1.68 trillion naira in 2018 alone. Banks as market participants in the Nigerian lease industry finance other non-bank lessors while the non-bank lessors account for about 80% of lease transactions mostly to Micro, Small and Medium Scale Enterprises (MSMEs). Funding remains a major challenge restricting provision of leases to general supporting equipment and constraining leases of specialized assets (big-ticket leases). Prospects for lease finance obtain in terms of rising popularity of operating leases with lessors and lessees, attributable to the inherent mitigation against default risk. There is also potential for a growing customer base beyond MSMEs, with the influx of patronage by listed corporate firms especially those in the healthcare and education sectors. We identified financing partnerships, development of sound corporate governance practices, hastened inauguration of the Equipment Leasing Registration Authority and increased sensitization of potential leasehold product consumers on the benefits of lease finance, as critical success factors for the lease industry in Nigeria.